A STUDY OF THE ACTIVITY OF SOCIAL ENTERPRISES IN BULGARIA - R. Martinov; E. Maslarova; K. Benkova (Trakia Journal of Sciences)
Many companies in Bulgaria are defined themselves as Social enterprises (SE). The process of arising of new SE and their stop of working is a significant challenge. The situation with SE is very dynamic and their real status should be studied to estimate their impact on the Bulgarian economy. Here we describe the real picture of SE in Bulgaria, based on officially published data. In result of data analysis we make conclusions and estimations in order to stabilize these processes. The strong dominance of Sofia (Capital) was detected in both Non-financial (NFE) and Non-for-profit (NPE) sectors of SE. It could be further ascertain if the operations are really in Sofia city or only their registration. Lightly positive trend was found in the number of both NFE and NPE. Highly negative was the trend in the number of employees engaged in NFE, while the NPE sector remained relatively stable. This deviation in employment rate could be explained by a type of funding: NPE were funded predominantly by state or EU projects, while NFE tried to keep the enterprises and balanced by lowering the personnel, probably due to insufficient financing and economic crisis. In conclusion, more attention in needed by the government and the EU regarding the funding of NFE.